Peran Preferensi Influencer sebagai Sumber Kredibilitas pada Produk Make Up Wardah terhadap Niat Pembelian Konsumen - Perangin Angin, Pettia Weharima; Masithah, Siti Nur (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the influence of consumer preferences for influencers promoting Wardah makeup products on purchase intention. Social media influencers play a key role in shaping consumer perceptions and decisions, particularly in the beauty industry. The study applies the source credibility theory, which includes three main dimensions: attractiveness, trustworthiness, and expertise. A survey was conducted with 70 social media users in Indonesia aged 20–50, representing Wardah’s target market. The results show that all three dimensions have a positive impact on purchase intention, although not all are statistically significant. Influencer attractiveness captures consumer attention and encourages positive perceptions of the product. Trustworthiness is crucial, as consumers are more likely to follow recommendations from influencers perceived as honest and reliable. Expertise adds value, especially when consumers believe in the influencer’s knowledge in the beauty field. This study contributes to digital marketing literature by providing empirical evidence on how influencer credibility can effectively shape consumer purchasing decisions. The findings can help companies design more effective marketing strategies by leveraging high-credibility influencers to promote their products on social media.